Conceptos basicos de entomologia y manejo de plagas - Zuniga, T (United Nations Development Programme, 1985)
The natural factors affecting insect pest mortality are described as an important aspect in the regulation of populations. Through graphs of population density vs. time, the position of equilibrium of an insect population, the economic threshold, and the level of economic damage are indicated. General aspects of var. resistance are discussed, namely: antixenosis, tolerance, and antibiosis, the latter regarding Apion godmani and Empoasca kraemeri. (CIAT)